2017
DOI: 10.1111/anu.12611
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of heat-inactivated Bacillus clausii DE5 in diets for grouper, Epinephelus coioides, improves feed utilization, intestinal and systemic immune responses and not growth performance

Abstract: In recent years, more and more attentions have been paid to the development and application of probiotics in aquaculture, and viable probiotics have been extensively studied, while rare information was available about inactivated probiotics in aquaculture. Therefore, in this study, a feeding trial was designed to investigate the effect of dietary supplementation of heat-inactivated probiotic Bacillus clausii DE5 on growth performance, immune response and key immune genes expression in head kidney and intestine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 60 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…In the present study, taurine levels up to 0.50 g/kg diet increased the LZ and ACP activities, C3, C4 and IgM contents, as well as up‐regulated the mRNA levels of hepcidin, LEAP‐2A, LEAP‐2B, β‐defensin‐1 and MUC2 in the three intestinal segments of young grass carp, implying that taurine supplementation could improve the intestinal immune function of fish. In addition, the immune function of fish is also related to inflammatory response, which is primarily mediated by cytokines (Abdelrazek, Tag, Kilany, Reddy, & Hassan, ; Wang et al, ). Hence, we next systematically investigated the effects of taurine supplementation on cytokines in the intestines of fish.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, taurine levels up to 0.50 g/kg diet increased the LZ and ACP activities, C3, C4 and IgM contents, as well as up‐regulated the mRNA levels of hepcidin, LEAP‐2A, LEAP‐2B, β‐defensin‐1 and MUC2 in the three intestinal segments of young grass carp, implying that taurine supplementation could improve the intestinal immune function of fish. In addition, the immune function of fish is also related to inflammatory response, which is primarily mediated by cytokines (Abdelrazek, Tag, Kilany, Reddy, & Hassan, ; Wang et al, ). Hence, we next systematically investigated the effects of taurine supplementation on cytokines in the intestines of fish.…”
Section: Discussionmentioning
confidence: 99%
“…2010); Bacillus circulance (Bandyopadhyay & Das Mohapatra 2009); Bacillus clausii (Wang et al . 2018); Bacillus coagulans (Pan et al . 2013); Bacillus pumilus (Aly et al .…”
Section: Bacillus Group Of Probiotics With Reference To Bacillus Subtmentioning
confidence: 99%
“…Among others, B. subtilis is the most studied and widely used species (Farzanfar et al 2009;Wu et al 2012;Keysami & Mohammadpour 2013;Fan et al 2013a). Besides, several other Bacillus species such as Bacillus aryabhattai (Tepaamorndech et al 2019); Bacillus cereus (Lalloo et al 2010); Bacillus circulance (Bandyopadhyay & Das Mohapatra 2009); Bacillus clausii (Wang et al 2018); Bacillus coagulans (Pan et al 2013); Bacillus pumilus (Aly et al 2008a); Bacillus siamensis (Meidong et al 2017); Bacillus thuringiensis (Anyanwu & Ariole 2019); and Bacillus velezensis (Li et al 2019) are also used in aquaculture.…”
Section: Bacillus Group Of Probiotics With Reference To Bacillus Subtmentioning
confidence: 99%
“…Numerous studies have revealed that supplementation of Bacillus to the diet improved growth performance, digestive enzyme activities, antioxidant function, immune responses, and disease resistance of fish [28,[52][53][54][55][56][57][58]. The Bacillus species used include Bacillus subtilis [59][60][61][62][63], Bacillus cereus [51,64,65], Bacillus amyloliquefaciens [56], Bacillus baekryungensis [66], Bacillus licheniformis [27,28,67], Bacillus pumilus [22,52,68], Bacillus clausii [52,69], Bacillus coagulans [25,26,29,58,70], and Bacillus velezensis [71].…”
Section: Bacillusmentioning
confidence: 99%
“…Yan et al demonstrated that heat-inactivated B. pumilus SE5 could effectively improve growth performance and remarkably upregulated expression of TLR2 and pro-inflammatory cytokines (IL-8 and IL-1β) in head kidney of grouper (Epinephelus coioides) [68]. More recently, Wang et al revealed that heat-inactivated B. clausii DE5 improved feed utilization and the expression of TLR5, pro-inflammatory cytokines (IL-8 and IL-1) and TGF-1 in the head kidney and intestine of grouper [69].…”
Section: Bacillusmentioning
confidence: 99%